Ecological aspects of the floral phenology of the cork-oak (Q suber L): why do annual and biennial biotypes appear? - Elena-Rossello, J. A.; de Rio, J. M.; Valdecantos Garcia, J. L.; Santamaria, I. G. (Ann. For. Sci., 1993)
Phenological observations (periods of flowering and pollination, floral structures, etc) were made over a 3-year period in natural populations of Q suber. We demonstrated the existence of 2 different types of seed cycles in the cork-oak. The 'annual biotype', requires only 1 season to complete its reproductive cycle (ie, similar to that of the Lepidobalanus group), whereas the 'biennial biotype' requires 2 full years (similar to Erythrobalanus). The variability observed in the cork-oak, during the reproductive cycle, and the meaning of the existence of 2 different reproductive strategies in the same species, are discussed
Keywords: annual and biennial biotypes; cork-oak; ecological variability; floral phenology; Quercus; reproductive strategies